E-filing acceptance by the individual taxpayers : a preliminary analysis / Nor ‘Azimaton Saibon, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin - Saibon, Nor ‘Azimaton; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Universiti Teknologi MARA, Shah Alam, 2016)
The objective of this study is to determine taxpayer’s perception on the tax filing system via internet, or well known as e-Filing. The samples were randomly selected from various taxpayers that walk in Inland Revenue Board Petaling Jaya Branch. Survey questionnaires were hand distributed with 44 taxpayers responded. The data collected were analyzed by using descriptive statistic. After 8 years of implementation, the respondents agreed that e-Filing is user friendly and easy to use. Based on the findings, majority of the taxpayers also have confidence and used e-Filing to file their tax return form, indicating taxpayers have a good perception toward e-Filing. However, they are concerned on the safety and security of the system and the efficiency of the server to operate particularly during the peak period.